The Influence of School Principal Leadership on The Improvement of Literacy and Numeracy Achievements Based on Education Reports at Junior High School - Faisal, Agus; Mustofa; Baijuri; Badrudin; Apriani, Hikma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This article analyzes the influence of the principal's leadership on improving literacy and numeracy achievements at Junior High School, using Education Report data from 2022 to 2025. Employing a qualitative descriptive approach with document analysis and interviews involving 10 teachers and the school principal, the study examines how leadership practices affect student learning outcomes. The findings reveal a substantial increase in literacy achievement from 51.11% in 2022 to 86.67% in 2025, and in numeracy from 31.11% to 74.42% over the same period. This progress is attributed to the principal’s strategic focus on data-based learning, consistent academic supervision, and teacher empowerment. By systematically analyzing educational data, the principal identifies learning gaps and implements targeted interventions. Academic supervision sessions enhance pedagogical practices, while structured professional development fosters teacher innovation. Furthermore, the principal cultivates a collaborative culture where teachers share best practices and engage in continuous training. These results highlight the principal's role as a change agent who fosters a supportive and high-achieving school environment. The study underscores the importance of effective leadership in strengthening educational quality, particularly in literacy and numeracy. It recommends that school leaders adopt evidence-based strategies and prioritize teacher development to drive sustainable learning improvements.